The Impact of Gold Returns, Bitcoin Returns, and Rising Food Price on Hedging Capability Against Education Costs in Indonesia - Dzulfikar S. Rambe, Tuani; Alli, Hafzi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the effectiveness of gold and Bitcoin as hedging instruments against the rising costs of education and food inflation in Indonesia. Using data from 2009 to 2024, the research employs descriptive and correlational quantitative methods, incorporating volatility analysis and hedging effectiveness models such as the Sharpe ratio and Value-at-Risk. Gold demonstrates stability and consistent performance as a hedge against inflation in education costs, while Bitcoin, despite its volatility, shows potential as a speculative alternative. Food price increases are shown to significantly impact education costs, and this study highlights the need for effective investment strategies to counteract these economic challenges. The findings contribute to a deeper understanding of gold and Bitcoin's roles in mitigating specific forms of inflation, particularly in critical sectors like education and food.